Designing and conducting tabletop exercises to assess public health preparedness for manmade and naturally occurring biological threats - Dausey David J; Buehler James W; Lurie Nicole (BMC, 2007)
Abstract Background Since 2001, state and local health departments in the United States (US) have accelerated efforts to prepare for high-impact public health emergencies. One component of these activities has been the development and conduct of exercise programs to assess capabilities, train staff and build relationships. This paper summarizes lessons learned from tabletop exercises about public health emergency preparedness and about the process of developing, conducting, and evaluating them. Methods We developed, conducted, and evaluated 31 tabletop exercises in partnership with state and local health departments throughout the US from 2003 to 2006. Participant self evaluations, after action reports, and tabletop exercise evaluation forms were used to identify aspects of the exercises themselves, as well as public health emergency responses that participants found more or less challenging, and to highlight lessons learned about tabletop exercise design. Results Designing the exercises involved substantial collaboration with representatives from participating health departments to assure that the scenarios were credible, focused attention on local preparedness needs and priorities, and were logistically feasible to implement. During execution of the exercises, nearly all health departments struggled with a common set of challenges relating to disease surveillance, epidemiologic investigations, communications, command and control, and health care surge capacity. In contrast, performance strengths were more varied across participating sites, reflecting specific attributes of individual health departments or communities, experience with actual public health emergencies, or the emphasis of prior preparedness efforts. Conclusion The design, conduct, and evaluation of the tabletop exercises described in this report benefited from collaborative planning that involved stakeholders from participating health departments and exercise developers and facilitators from outside the participating agencies. While these exercises identified both strengths and vulnerabilities in emergency preparedness, additional work is needed to develop reliable metrics to gauge exercise performance, inform follow-up action steps, and to develop re-evaluation exercise designs that assess the impact of post-exercise interventions.